Heparin-Mimicking Polymer Modified Polyethersulfone Membranes - A Mini Review - Xiang, Tao; Cheng, Chong; Zhao, Changsheng (Journal of Membrane and Separation Technology, 2014)
Recent studies on the modification of polyethersulfone (PES) membranes using heparin-mimicking polymers are reviewed. The general conception of heparin-mimicking polymersis defined as the syntheticpolymers (including the biopolymer derivates and synthetic sulfated artificial polymers) with similar biologically functionalities as heparin, such as the anticoagulant, growth factor binding, and also disease mediation. In the review, heparin-mimicking polymers is briefly reviewed; then heparin-mimicking polymer modified PES membranes, including blended, coated, and grafted membranes are discussed respectively.